Estimation Of Genetic Divergence In Lablab Bean (Lablab purpureus L.) Genotypes (Bangladesh Journal of Agricultural Research, 2013)
An experiment for diversity analysis with 66 genotypes of lablab bean (Lablab purpureus L.) was conducted at Department of Genetics and Plant Breeding, Bangladesh Agricultural University (BAU) during 2009-2010. Data were collected from all experimental plants on the following characters: days to first flowering, days to 50% flowering, days to first pod setting, no. of pods per plant, wt. of 20 pods (g), pod yield per plant (g), pod length (cm), number of seeds per pod, number of seeds per plant, 100-seed weight (g), and seed yield per plant (g). As per multivariate analysis, the genotypes were grouped into seven clusters. The highest number of genotypes 15 was included in cluster V followed by cluster II, which contained 13 genotypes. Cluster III, I, VI, IV contained 12, 11, 6, and 5 genotypes, respectively. The cluster VII which included 4 genotypes was the smallest among the 7 clusters. It is important to note that the highest amount of genetic divergence within the cluster group was noticed in the cluster VII having only 4 genotypes. The inter-cluster distances (D2) were higher than the intra-cluster distances. The inter-cluster D2 values varied from 2059.094 to 19302.6. The distances between the cluster VII and V; VII and VI; VII and II and VII and I were comparatively high than the other inter-cluster distances. The genotypes of these clusters were thus more diversified for yield and yield contributing characters. The intracluster distance (8502.795) observed in cluster VII revealed maximum diversity among themselves. While the least variation (625.372) was noticed between genotypes of the cluster II signifying the closeness of the genotypes included in this cluster. Data on the contribution of individual characters towards divergence suggested that no. of pods per plant contributed maximum (34.033%) to the genetic divergence followed by pod yield per plant and 100-seed weight. The genotypes of the cluster VII produced highest pods per plant and those of the cluster II produced lowest pod yield per plant. Seed yield per plant was found to be highest in cluster VII and lowest in cluster II. Results of the study suggested that selection for these traits in climbing genotypes might be effective. By strategically using this diversity, the breeder can develop high yielding varieties of lablab bean. Bangladesh J. Agril. Res. 38(1): 105-114, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15195